2020
DOI: 10.1111/dth.14310
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, open label, multicenter, postmarket study evaluating Princess VOLUME Lidocaine for the correction of nasolabial folds

Abstract: The aim of this study was to investigate the safety and performance of Princess VOLUME Lidocaine in nasolabial fold correction. In this prospective, open label, multicenter, postmarket study subjects received injections of Princess VOLUME Lidocaine into both NLF at Baseline (Day 0) and if considered necessary by the investigator, at Week 2 (touch-up treatment). This study was conducted in Austria at the Department of Dermatology and Venereology, Medical University of Graz, at the medical aesthetic center MÄZ W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The safety assessments demonstrated that both Restylane and Yishumei were safe and tolerable, and there was no significant difference in the incidence of AEs between the two HA fillers or between the superficial and deep injections. The most common AEs were swelling, redness, and tenderness at the injection site, which were also described in previous studies, 22 but all the AEs were selflimiting and resolved spontaneously without treatment. There was one case of unexpected pregnancy at week 12, but no AEs occurred in this participant through the 52 weeks of observation.…”
Section: Safetysupporting
confidence: 81%
“…The safety assessments demonstrated that both Restylane and Yishumei were safe and tolerable, and there was no significant difference in the incidence of AEs between the two HA fillers or between the superficial and deep injections. The most common AEs were swelling, redness, and tenderness at the injection site, which were also described in previous studies, 22 but all the AEs were selflimiting and resolved spontaneously without treatment. There was one case of unexpected pregnancy at week 12, but no AEs occurred in this participant through the 52 weeks of observation.…”
Section: Safetysupporting
confidence: 81%
“…The inclusion criteria for nasolabial fold severity ranged from mild to extreme, following Kopera et al, 10 and for jawline sagging, it ranged from mild to very severe, as per Pooth et al 11 The treatment direction primarily targeted the superior and lateral areas of the face, especially for the nasolabial fold and jowl fat approaching from the skin surface. Each participant underwent up to three treatments at 3‐week intervals.…”
Section: Methodsmentioning
confidence: 99%